Model Pengembangan Manajemen Sdm Masjid Di Kota Medan - Joli Afriany; Hubbul Wathan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2019)
The purpose of this study is to determine the management of the mosque in developing the quality of human resources in the Aceh Sepakat Mosque in Medan. The development of human resources is a factor needed in preaching activities both in terms of individuals or organizations so that the achievement of objectives that are carried out effectively and efficiently, therefore the management is must use good management. The mosque's existence is needed by the community, considering the mosque is one of the religious institutions whose role and function is not only for religious activities, but can be used for social activities and community empowerment around and also the development of the community . This study used qualitative research methods. Field research is research using information obtained from informants or respondents through data collection techniques using observation, interviews and documentation. After conducting research, it is known that mosque management in developing the quality of human resources in Aceh agreed to implement managerial functions, which include planning , organizing, mobilizing and monitoring. Then implement operational functions, which include procurement, development, compensation, integration and maintenance. As for the development of human resources, which is carried out with the holding of training in addition, the board is also involved in the committees of competitions, recitation and other activities